2003
DOI: 10.2105/ajph.93.11.1915
|View full text |Cite
|
Sign up to set email alerts
|

Regional Patterns and Correlates of Substance Use Among Young Men Who Have Sex With Men in 7 US Urban Areas

Abstract: Effective drug prevention and treatment programs addressing local drug-use patterns and associated factors are urgently needed for young MSM, a population with a high rate of illicit drug use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
165
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(186 citation statements)
references
References 31 publications
17
165
4
Order By: Relevance
“…Although average levels of use of methamphetamines, poppers, or sniffed cocaine did not increase over the duration of the trial, younger MSM were more likely to report increasing use of these drugs. Given the high rates of drug use reported by young MSM, with up to 66% reporting illicit drug use in the prior 6 months, 3 and their high risk for HIV infection, 23 these findings substantiate the need for HIV prevention interventions that reach and engage young drug-using MSM, and for HIV prevention programs targeting young MSM to stress the link between drug use and sexual risk behavior. Intervening among younger populations presents many challenges, but present opportunities to reduce sexual and drug-use behavior in early adulthood, thereby preventing the long-term sequelae of these risky behaviors.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Although average levels of use of methamphetamines, poppers, or sniffed cocaine did not increase over the duration of the trial, younger MSM were more likely to report increasing use of these drugs. Given the high rates of drug use reported by young MSM, with up to 66% reporting illicit drug use in the prior 6 months, 3 and their high risk for HIV infection, 23 these findings substantiate the need for HIV prevention interventions that reach and engage young drug-using MSM, and for HIV prevention programs targeting young MSM to stress the link between drug use and sexual risk behavior. Intervening among younger populations presents many challenges, but present opportunities to reduce sexual and drug-use behavior in early adulthood, thereby preventing the long-term sequelae of these risky behaviors.…”
Section: Discussionmentioning
confidence: 78%
“…20 Our finding that Latino participants were less likely to report use of these drugs compared with white participants is consistent with other studies. 3,21 These findings reinforce the importance of recognizing that drug-use patterns vary among racial/ethnic groups of MSM, and that HIV prevention interventions need to be tailored accordingly.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…These increases are especially troubling because they follow a period of steadily declining rates of new infection among MSM, and suggest that existing prevention programming is not working, particularly in younger MSM cohorts. Among the factors contributing to this renewal in the growth of HIV infection rates in MSM populations, drug abuse has emerged as a significant contributing factor, both in relation to sexual risk as well as in the context of injection-mediated transmission risk (c.f., Thiede et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the CDC's Young Men's Survey (YMS) almost 90% of 15-22 year old MSM reported using alcohol, 66% reported illicit drug use, 29% used drugs on a regular basis, and 28% reported polydrug use (all in the 6 months prior to the interview) (16). A comparisons of YMS data to general population samples of youth concluded that rates of alcohol use were similar, but rates of illicit drugs were higher (16). Rates of mental illness among YMSM are difficult to estimate because sexual orientation has not been assessed in major epidemiological studies of youth mental health.…”
mentioning
confidence: 99%